“Hollow at the core”:: Deconstructing Yann Martel’s Life of Pi - Stratton, Florence (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2004)
The deconstructive project of Yann Martel's Life of Pi is to replace the Enlightenment belief in the power of reason to liberate humanity with a belief in the transforming power of story. By employing the techniques of realism in fusing mundane details with an "incredible" story, Martel gives formal expression to the reason-imagination, fact-fiction debate at the centre of the novel. Life of Pi attempts not to prove God's existence, but to justify belief in Him, thereby calling into question the devaluing and displacement of imaginative truth by positivist notions of physical, material truth. That Pi shows little or nothing in the way of personal growth, however, seriously compromises this project, calling attention to the epistemological and political limitations of the postmodernist view of language's equivocal relation to reality.